2012
DOI: 10.1371/journal.pone.0030442
|View full text |Cite
|
Sign up to set email alerts
|

Association between Variations in Cell Cycle Genes and Idiopathic Pulmonary Fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is a devastating and progressive lung disease. Its aetiology is thought to involve damage to the epithelium and abnormal repair. Alveolar epithelial cells near areas of remodelling show an increased expression of proapoptotic molecules. Therefore, we investigated the role of genes involved in cell cycle control in IPF. Genotypes for five single nucleotide polymorphisms (SNPs) in the tumour protein 53 (TP53) gene and four SNPs in cyclin-dependent kinase inhibitor 1A (CDKN1A),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 32 publications
3
29
0
1
Order By: Relevance
“…Numerous other polymorphisms, for example on TLR9, have been associated with IPF [93][94][95]. More recently, genome-wide pulmonary fibrosis association studies have not only confirmed the association between IPF and MUC5B, TERT or TERC but have also revealed several new locations of interest [96][97].…”
Section: Genetic and Epigenetic Polymorphismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous other polymorphisms, for example on TLR9, have been associated with IPF [93][94][95]. More recently, genome-wide pulmonary fibrosis association studies have not only confirmed the association between IPF and MUC5B, TERT or TERC but have also revealed several new locations of interest [96][97].…”
Section: Genetic and Epigenetic Polymorphismsmentioning
confidence: 99%
“…De nombreux autres polymorphismes par exemple sur TLR9 ont été associés à la FPI [93][94][95]. Plus récemment des études d'association génome entier-fibrose pulmonaire ont d'abord confirmé l'association entre la FPI et MUC5B, TERT ou TR mais ont aussi mis en évidence plusieurs nouveaux locus d'intérêt [96][97].…”
Section: Polymorphismes Génétiques Et éPigénétiquesunclassified
“…associated with rapid progression of idiopathic pulmonary fibrosis, 32 increased risk of death in non-small cell lung cancer, 33 and joint involvement in systemic lupus erythematosus. 34 It is plausible that variants in CDKN1A might play a similar role in disease progression of NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have indicated that the abnormalities in the ability of epithelial cells to divide and replace epithelia could be central to the pathophysiology of disease [34-36*], and correspondingly genetic variants in cell cycle genes have been associated with IPF and disease progression [37]. …”
Section: Introductionmentioning
confidence: 99%